1985
DOI: 10.1016/0014-5793(85)80391-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of the K+ channel blockers apamin and quinine on glucose‐induced electrical activity in pancreatic β‐cells from a strain of ob/ob (obese) mice

Abstract: The effects of apamin and quinine on glucose-induced electrical activity in pancreatic islets from ob/ob mice (Norwich colony) were compared. Apamin (40-400 nM) increased the duration of the bursts of electrical activity, whereas quinine (SO-100 PM) affected only slightly the steady-state electrical response to glucose. This sensitivity to apamin and poor response to quinine contrast with the resistance to apamin and sensitivity to quinine previously reported for pancreatic islets from albino mice. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…Among other features, this electrical pattern is characterized by a higher sensitivity to low glucose concentrations. This hyper-excitability has been related to altered K + permeabilities (Fournier et al, 1990;Rosario, 1985). These observations would be in accordance with the lower density of KATP channels in the membrane of β-cells from ob/ob mice (Park et al, 2013).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Among other features, this electrical pattern is characterized by a higher sensitivity to low glucose concentrations. This hyper-excitability has been related to altered K + permeabilities (Fournier et al, 1990;Rosario, 1985). These observations would be in accordance with the lower density of KATP channels in the membrane of β-cells from ob/ob mice (Park et al, 2013).…”
Section: Discussionsupporting
confidence: 68%
“…Statistical significance is indicated: ***p ≤ 0.001. Rosario, 1985;Rosario et al, 1985). It has been reported that higher action potentials may be associated to increased inward Ca 2+ currents due to the voltage-dependence characteristics of Ca 2+ channels (Gonzalez et al, 2013;Houamed et al, 2010;Jacobson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The apparent lack of effect of 4-AP on the voltage-sensitive K+ permeability of/3-cells (at concentrations that did not reduce the glucose metabolism) is not unique. In this sense, apamin, a Ca2+-dependent K+ permeability blocker, also failed to effect this permeability in /-cells from normal rats and mouse (Lebrun, Atwater, Claret, Malaisse & Herchuelz, 1983;Rosa'rio, 1985) but not from obese mice (Rosario, 1985). Finally, the present observation also agrees with the findings of , where a delayed outward K+ current induced in single mouse ,-cells was completely blocked by 20 mm TEA but only partialy blocked by 5mM 4-AP.…”
Section: Discussionsupporting
confidence: 91%
“…Elec trophysiological tests have shown that integrity of ion channels may be impaired in pancreatic islets of obob mice (161). Islets from obese mice were characterized by a more depolarized membrane than were those in lean mice (160). Quinine, which blocks the ATP-sensitive K + -activated ion channel, and apamin, which blocks the Ca 2+ -activated K + channel, have atypical effects on islets from obese mice.…”
Section: Ratsmentioning
confidence: 99%